2022
DOI: 10.1111/neup.12846
|View full text |Cite
|
Sign up to set email alerts
|

The landscape of common genetic drivers and DNA methylation in low‐grade (epilepsy‐associated) neuroepithelial tumors: A review

Abstract: Low-grade neuroepithelial tumors (LNETs) represent an important group of central nervous system neoplasms, some of which may be associated to epilepsy. The concept of long-term epilepsy-associated tumors (LEATs) includes a heterogenous group of low-grade, cortically based tumors, associated to drug-resistant epilepsy, often requiring surgical treatment. LEATs entities can sometimes be poorly discriminated by histological features, precluding a confident classification in the absence of additional diagnostic to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 106 publications
(574 reference statements)
0
2
0
Order By: Relevance
“…LNETs are a group of slowly growing and low‐grade central nervous system neoplasms that exhibit varying levels of glial and/or neuronal differentiation 1,2 . These tumors are the most common tumor entities associated with epilepsy in children and young adults and have indolent behavior and variable morphology, including infiltrative growth and frequent calcification 3 .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…LNETs are a group of slowly growing and low‐grade central nervous system neoplasms that exhibit varying levels of glial and/or neuronal differentiation 1,2 . These tumors are the most common tumor entities associated with epilepsy in children and young adults and have indolent behavior and variable morphology, including infiltrative growth and frequent calcification 3 .…”
Section: Figurementioning
confidence: 99%
“…Contrast-enhanced MRI showed that the mass was clearly intramedullary and solid without marginal enhancement, and the signal had no increase on T1-weighted images and T2-weighted images compared with the normal cord ( LNETs are a group of slowly growing and low-grade central nervous system neoplasms that exhibit varying levels of glial and/or neuronal differentiation. 1,2 These tumors are the most common tumor entities associated with epilepsy in children and young adults and have indolent behavior and variable morphology, including infiltrative growth and frequent calcification. 3 In addition, they are characterized by oligodendrogliomalike components, aberrant CD34 expression, and frequent mitogen-activated protein kinase pathway activation.…”
mentioning
confidence: 99%